Heavy-ion collisions at the LHC—last call for predictions - Armesto, N; Borghini, Nicolas; Jeon, S; Wiedemann, UA; Abreu, S; Akkelin, SV; Alam, J; Albacete, JL; Andronic, A; Antonov, D; others (Journal of Physics G: Nuclear and Particle Physics, 2008)
n/a
n/a